2019
DOI: 10.1111/1911-3846.12486
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Auditor Report Changes on Financial Reporting Quality and Audit Costs: Evidence from the United Kingdom

Abstract: While substantial revisions to auditor reporting requirements are being implemented internationally, the impact of these reforms on financial reporting quality is unknown. We exploit the United Kingdom's recent auditor reporting changes and find that the United Kingdom's new reporting regime is associated with an improvement in financial reporting quality as proxied by significant decreases in absolute abnormal accruals and the propensity to just meet or beat analyst forecasts, and a significant increase in ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
211
5
25

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(336 citation statements)
references
References 58 publications
17
211
5
25
Order By: Relevance
“…In addition to the research on whether the audit report reform or key audit matters can bring incremental information value, there are also research and Analysis on the impact of disclosure of key audit matters or audit report reform on audit quality and audit cost. Reid et al (2019) takes the reform of audit report in the UK as the background, and proves that the reform of audit report improves the quality of financial report, but does not cause the increase of audit cost, and affirms the significance of the reform of audit report. However, Gutierrez et al (2018) believe that disclosure of risks alone will not lead to the improvement of audit quality or audit fees, but this conclusion may be because the long-term impact of audit report changes has not been captured.…”
Section: Literature Review On Key Audit Mattersmentioning
confidence: 80%
“…In addition to the research on whether the audit report reform or key audit matters can bring incremental information value, there are also research and Analysis on the impact of disclosure of key audit matters or audit report reform on audit quality and audit cost. Reid et al (2019) takes the reform of audit report in the UK as the background, and proves that the reform of audit report improves the quality of financial report, but does not cause the increase of audit cost, and affirms the significance of the reform of audit report. However, Gutierrez et al (2018) believe that disclosure of risks alone will not lead to the improvement of audit quality or audit fees, but this conclusion may be because the long-term impact of audit report changes has not been captured.…”
Section: Literature Review On Key Audit Mattersmentioning
confidence: 80%
“…The possible reason is that the disclosure of key audit matters is gradually compulsory, which will not lead to the increase of audit fees. Reid et al (2019) took advantage of recent changes in UK audit reports and found no empirical evidence of significant changes in audit quality or audit costs when implementing the new reporting system.…”
Section: The Impact On Auditorsmentioning
confidence: 99%
“…The empirical findings are not found in the implementation of the new reporting system. There is empirical evidence of major changes in audit quality (Reid et al, 2019).…”
Section: The Impact On Auditorsmentioning
confidence: 99%
“…Whereas some archival and survey studies have investigated the impact of KAMs on the information content of expanded audit reports (Boolaky & Quick, 2016;Guttierez, Minutti-Meza, Tatum, & Vulcheva, 2018;Lennox, Schmidt, & Thompson, 2018;Reid, Carcello, Li, & Neal, 2018) and on auditor liability (for a review, see Gimbar, Hansen, & Ozlanski, 2016), only a few studies have analyzed the impact of the new auditor reporting requirement on the process of the audit itself -for exceptions, see Fuller (2015) and Cade and Hodge (2014); and for a comprehensive review of the current research, see Bédard, Coram, Espahbodi, and Mock (2016).…”
mentioning
confidence: 99%